Theory and applications of formal argumentation : third International Workshop, TAFA 2015, Buenos Aires, Argentina, July 25-26, 2015, Revised selected papers /: third International Workshop, TAFA 2015, Buenos Aires, Argentina, July 25-26, 2015, Revised selected papers. (2015) - Unknown
No abstract available